Pelatihan Strategi Pemesaran Produk Sagu di Kelurahan Guraping Kecamatan Oba Utara - Ida Hidayanti; Sulfi Abdul Haji; Fadliah M.Alhadar; Musdar Muhammad (Jurnal Pengabdian Masyarakat, 2025)
This Community Service (PkM) activity was carried out with the primary objective of empowering sago entrepreneurs in Guraping Village by increasing their capacity to implement modern marketing strategies. The program was held on Thursday, May 22, 2025, and involved 25 participants, consisting of sago artisans, MSMEs, and local community representatives. The implementation method included outreach, face-to-face training, and direct mentoring on digital marketing strategies, including the use of e-commerce (marketplaces) and social media platforms such as Instagram, Facebook, and TikTok as promotional tools for processed sago products. The results of the activity demonstrated an increase in participants’ knowledge and skills in understanding digital marketing concepts and the importance of product branding. Furthermore, participants were able to create business accounts and independently upload products to online platforms. This activity emphasized that the success of local business development depends heavily on collaboration between academics, entrepreneurs, and local government support in providing supporting facilities and regulations. Through this activity, it is hoped that sago entrepreneurs in Guraping can increase their competitiveness, expand their market reach, and ultimately increase income and community welfare sustainably.